# I tried to solve this problem but I can't seem to get v-(4-v)=-2(2v-1)?

v-(4-v)=-2(2v-1)

Relevance

v-(4-v)=-2(2v-1)

v-4+v=-4v+2

2v-4=-4v+2

2v+4v=2+4

6v=6

checking

1-(4-1)=-2(2(1)-1)

1-3=-2(2-1)

-2=-2 check

• Okay, easy! Just get a piece of paper. Now, write down the equation: v-(4-v)=-2(2v-1). Then, multiply the -2(2v-1) so that is -4v+2 so now the equation is: v - 4 + v = -4v + 2, subtract a v from each side, so now it is: -4-v=-5v+2 then, add a v to each side so the v's cancel out on the left and it becomes -4v on the right, the equation is now: -4=-4v+2. then subtract 2 from each side, and u get -6=-4v divide by -4 on each side, so you get 1=v

And that should be the answer!

:) Hope i helped!

<3

• v-4v+v=-4v+2 (this is the first step when you get all the stuff out of ( )

6v=6 (bringing terms to the correct sides of equation)

v=1

Hope that helps!

• I take the question as v-(4-v)=-2(2v-1)

Open brackets to get v-4+v = -4v+2

Group like terms to get v+v+4v = 2+4

Simplify to get 6v = 6

and hence v = 1.

• v-(4-v)=-2(2v-1)

v - 4 + v = -4v + 2

2v + 4v = 2 + 4

6v = 6

v = 1

• Anonymous

-4+2v=-4v+2

v=1

• v - (4-v) = -2(2v-1)

v - 4 + v = -4v + 2

2v -4 = -4v + 2

6v = 6

v = 1.

• v-(4-v)=-2(2v-1)

v-4+v = -4v +2

2v-4 = -4v+2

2v+4v = 2+4

6v = 6

v= 1

• v - 4 + v = -4v + 2

2v - 4 = -4v + 2

6v = 6

v = 1

• v - 4+v = -4v +2

2v - 4 = -4v + 2

6v = 6

v = 1